The uniqueness of the best $L_1$-approximant of continuous Banach-valued functions under interpolatory constraints - M.Ye. Tkachenko; V.M. Traktynska (Researches in Mathematics)
We consider the best $L_1$-approximation with interpolatory constraints for continuous mapping of a metric compact set $Q$ into a Banach space $X$. The unicity set’s criterion is obtained. This result generalizes the result for real functions that was proved by A. Pinkus and H. Strauss.